PENERAPAN MEDIA KARTU KATA UNTUK MENINGKATKAN KEMAMPUAN MENYUSUN PUISI BEBAS PADA PESERTA DIDIK KELAS V DI SDI KURUMBORO - sofiana Pano; Yohana Eufrosina Londa; Nurhaliza ahmad; Virgilius bate lina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is a Classroom Action Rsearch (CAR) aimed at improving the ability of fifth-grade students at SDI Kurumboro to compose free verse poetry through the application of word card media. The background of this studi is the low ability of students to independently write poetry, especially in terms of word choice, imagination development, and expressing feelings through literary language. Many students experience difficulties in initiating and developing ideas when writing poems, caused bay the lack of varied teaching methods and the absence of learning media that stimulate students creativity. Therefore, word card media was chosen as a learning tool to trigger ideas, enrich vocabulary, and guide students ini composing poetry in a more structured and creative manner. This study was conducted on May 14, 2025, at SDI Kurumboro with a research subject of 15 fifth-grade students. The method used was Classroom Action Research, wich consisted of two cycles, each including planning, action, observation, and reflection stages. Data collection techinques included observation, interviews, documentation, and students poetry writing tests. The data were analyzed using descriptive and quantitative methods.